Tempus i norsk - en grammatisk og deiktisk kategori - Czarnecki, Przemysław (Folia Scandinavica Posnaniensia, 2007)
On the basis of the data selected from Norwegian newspapers the article sets out to describe general properties of the Norwegian tense system, focusing on the deicitic and grammatical character of the tense forms. A definition of deixis is offered and the difference between the past tenses and future tenses is put into perspective. By using Reichenbach’s logical symbols (moment of event, moment of speech and reference point), an attempt is made to show how Norwegian temporal relations can be described.